Coexpression of Fractalkine and Its Receptor in Normal Human Endometrium and in Endometrium from Users of Progestin-Only Contraception Supports a Role for Fractalkine in Leukocyte Recruitment and Endometrial Remodeling - Natalie J. Hannan; Rebecca L. Jones; Hilary Critchley; Gábor Kovács; Peter A. W. Rogers; Biran Affandi; Lois A. Salamonsen (2004)
Leukocytes are critical mediators of endometrial remodeling, but the mechanisms by which leukocyte subpopulations enter the uterus are currently unknown. Endometrial leukocytes have no genomic progesterone receptors; thus, we hypothesized that leukocyte migration is induced indirectly by progesterone-regulated chemokines. Fractalkine (CX3CL1), a chemotactic membrane-bound adhesion factor, and its receptor (CX3CR1) were assessed by immunohistochemistry in endometrial samples across the menstrual cycle, in early pregnancy, and in women using progestin-only contraceptives. Fractalkine was localized predominantly to glandular epithelial and decidualized stromal cells, with the highest staining intensity in the secretory phase and early pregnancy. It was also detected in subpopulations of endometrial leukocytes (macrophages and uterine NK cells), with maximal numbers during the proliferative phase and early pregnancy. CX3CR1 was similarly colocalized to the glandular epithelium and decidualized stromal cells, with the highest expression in the secretory phase. CX3CR1-positive leukocytes (macrophages and neutrophils) were in greatest abundance during the menstrual phase. In the endometrium of women using progestin-only contraceptives, immunoreactive fractalkine was markedly reduced in the glandular epithelium, but was increased in decidualized stroma and infiltrating leukocytes. These findings support a number of roles for fractalkine in the endometrium, in the secretory phase, in early pregnancy, and when influenced by progestin-only contraceptives.